Velocity based training: Validity of monitoring devices to assess mean concentric velocity in the bench press exercise - McGrath, G. A.; Flanagan, E. P.; O`Donovan, P.; Collins, D. J.; Kenny, I. C. (Journal of Australian Strength and Conditioning, 2018)
The purpose of this investigation was to determine the concurrent validity of two devices used in velocity-based monitoring of resistance training. The TendoTM Fitrodyne is a linear position transducer (LPT) which attaches to the barbell to measure velocity of movement. PUSHTM is a wearable inertia sensor (WIS) that is worn on the athlete`s forearm and utilizes an integrated gyroscope and accelerometer to provide a value for movement velocity. Both devices were compared with 3D motion capture data. The validation of such devices is paramount as they are being more frequently used in a strength and conditioning and biomechanics setting. Ten subjects completed 2 sets of 6 repetitions on the barbell bench press at loads of 40% and 80% of 1RM. All subjects had a minimum of one year`s resistance training experience. Results for the LPT and the WIS were both strongly correlated with the criterion measure (ICC > 0.9). However the wearable inertia sensor (WIS) consistently displayed lower mean concentric velocity (0.06 - 0.50 m.s-1 lower) values than the criterion measure (%error - 29.17%) suggesting it is not a valid measure of mean concentric velocity in the bench press exercise. Conversely the LPT was deemed a valid velocity-based monitoring device for the chosen exercise.